PENGARUH KOMUNIKASI VERBAL GURU TERHADAP MOTIVASI BELAJAR ANAK USIA DINI TK SE-KELURAHAN PADANG SARAI - Anggreini, An Nisa Fitri; Mahyuddin, Nenny (Bunayya, 2026)
Teacher verbal communication plays an important role in enhancing early childhood learning motivation; however, its implementation in classroom practice is not always optimal. This finding aimed to identify the impact of teachers verbal communication on early childhood learning motivation in kindergartens in Padang Sarai Subdistrict. This finding implements a descriptive quantitative approach. A total of 30 teachers were used as samples taken using purposive sampling. Data collection applies a Likert scale questionnaire. were then analyze using descriptive statistics and simple linear regressions. The study proved a very strong positive correlation between teacher verbal communication and learning motivation (r = 0.875, p < 0.05). Regression analysis showed that teacher verbal communication significantly affected learning motivation, with R² of 0.766, indicating that 76.6% of the variance in children’s learning motivation was explained by teacher verbal communication. These findings confirm that teacher verbal communication is a key determinant of learning motivation in early childhood education.